2015
DOI: 10.1080/09291016.2015.1021153
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and work efficiency of nursing staff engaged in rotating shift work

Abstract: Occupational stress and stress-related performance impairment is a common feature among hospital nurses engaged in rotating shift work, particularly night work. This cross-sectional survey determined workplace stress and cognitive efficiency of nursing staff engaged in rotating shift work. One hundred twenty-two full-time staff nurses in three different government hospitals in West Bengal, India, were the participants. Perceived exertion, alertness, sleep duration and various performance tests were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, we found that higher work challenge perception was related to a reduced psychological distress in nurses, particularly for nurses that worked by shifts compared to nonshift-work nurses. These results are in accordance with literature, which indicate that shift work constitutes an important source of occupational stress for nurses that work by shifts, who experience high levels of psychological distress related to work (Jaradat et al, 2017), thus interfering with their work efficiency (Haldar & Sahu, 2015). Our findings reinforce the idea that perceiving shift work as a challenge instead of a threat constitutes an important protector factor for shift-work nurses' mental health.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we found that higher work challenge perception was related to a reduced psychological distress in nurses, particularly for nurses that worked by shifts compared to nonshift-work nurses. These results are in accordance with literature, which indicate that shift work constitutes an important source of occupational stress for nurses that work by shifts, who experience high levels of psychological distress related to work (Jaradat et al, 2017), thus interfering with their work efficiency (Haldar & Sahu, 2015). Our findings reinforce the idea that perceiving shift work as a challenge instead of a threat constitutes an important protector factor for shift-work nurses' mental health.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also frequently confirmed the negative effects of long-term shift work and high workload on fatigue (34,35). In this regard, a study indicated that job burnout and physical fatigue were higher among shift workers, compared to other nurses (22). Peter et al also showed that shift workers experienced higher levels of physical fatigue and job burnout, compared to daytime workers (38).…”
Section: Discussionmentioning
confidence: 98%
“…In comparison with other occupations, healthcare personnel (especially physicians, nurses, and healthcare assistants) are more prone to burnout due to their exposure to stressors including: thanatophobia (12); interpersonal problems (13); low social support (14); verbal and physical aggression and violence (15,16); poor hospital work environments (17); high workload (18); high number of patients per day (19); decision-making in emergency situations (based on insufficient information) and accepting responsibility for the consequences (20); exertion along with mental pressure to avoid any mistakes (21); and rotating shift work, particularly night work (22). Farsi et al (2014) conducted a study at Army University of Medical Sciences (AJA) hospitals of Tehran, Iran and showed that quality of nurses' working life was reversely related to EE and DPA (23).…”
Section: Introductionmentioning
confidence: 99%
“…This might be attributed to diurnal variation of depressive symptoms among the study participants or sleep deprivation [25]. Some research report that work impairment due to mental health issues such as job stress are worst in the late night and early morning shift workers [26]. The current study documents that patients whose work is a private business were more work impaired than those who work in governmental or private sectors.…”
Section: Discussionmentioning
confidence: 58%